Pastoral Inscriptions : Reading and Writing Virgil's Eclogues. - Breed, Brian W. (Classical literature and society., 2013)
Virgil's ""Eclogues"" represent the introduction of a new genre, pastoral, to Latin literature. Generic markers of pastoral in the ""Eclogues"" include not only the representation of the singing and speaking of shepherd characters, but also the learned density of the text itself. Here, Brian W. Breed examines the tension between representations of orality in Virgil's pastoral world and the intense textuality of his pastoral poetry. The book argues that separation between speakers and their language in the ""Eclogues"" is not merely pastoral preciosity. Rather, it shows how Virgil uses represen.